Penares sp sponge from Menjangan Island-water West Bali National Park: Isolation of Cytotoxic Compounds - Erna Prawita Setyowati; Sudarsono Sudarsono; Retno Murwanti (Majalah Obat Tradisional, 2017)
Sponges are multicellular animals which have cytotoxic compounds. In this study, isolation and cytotoxic activity of Penares sp sponge from Menjangan island-water West Bali National Park have been carried out. The results showed that chloroform extract and GF V Penares sp fraction were toxic according to Brine Shrimp Lethality Test method (each 85% and 63.3% mortality at 25μg/mL concentration). The isolation result of GF V fraction was obtained a compound (Spot 4) that is active as cytotoxic agent against T47D cells (IC50 of 12.7 ug/mL). Spot 4 is a terpenoid compound which has conjugated double bonds.